Effects of Lactic Acid Bacteria Additives on the Quality, Volatile Chemicals and Microbial Community of Leymus chinensis Silage During Aerobic Exposure - Liu, Yichao; Li, Yuyu; Lu, Qiang; Sun, Lin; Du, Shuai; Liu, Tingyu; Hou, Meiling; Ge, Gentu; Wang, Zhijun; Jia, Yushan (Frontiers in Microbiology, 2022)
Silage exposed to air is prone to deterioration and production of unpleasant volatile chemicals that can seriously affect livestock intake and health. The aim of this study was to investigate the effects of Lactobacillus plantarum (LP), Lactobacillus brucei (LB), and a combination of LP and LB (PB) on the quality, microbial community and volatile chemicals of Leymus chinensis silage at 0, 4, and 8 days after aerobic exposure. During aerobic exposure, LP had higher WSC and LA content but had the least aerobic stability, with more harmful bacteria such as Penicillium and Monascus and produced more volatile chemicals such as Isospathulenol and 2-Furancarbinol. LB slowed down the rise in pH, produced more acetic acid and effectively improved aerobic stability, while the combination of LP and LB had an intermediate effect. Correlation analysis showed that Actinomyces, Sphingomonas, Penicillium and Monascus were associated with aerobic deterioration, and Weissella, Pediococcus, Botryosphaeria and Monascus were associated with strong volatile chemicals. In conclusion, LB preserves the quality of L. chinensis silage during aerobic exposure, while LP accelerates aerobic deterioration.